1969
DOI: 10.2466/pms.1969.28.2.567
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Effects of Distraction, Competing Tasks and Cognitive Style on Attention Deployment

Abstract: The study dealt with the influence of drive content and cognitive style (field dependence) on the deployment of attention between two competing tasks. Ss were less able to call out letters in a random order when they simultaneously had to listen to a taped verbal passage (at one time with open sexual content and at another with more neutral content). The amount of recall of the verbal passage was positively correlated with the degree of decrease in randomness on the letter task. On the passage with sexual cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1975
1975
1997
1997

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…With only few exceptions (16,252), the authors of the above-mentioned studes reported results basically in accordance with Baddeley's original finding: with addtional task load, randomization performance deched. In some experiments, specifically the instruction to remember a distracting text (as opposed to simply read it) would lead to enhanced redundancy of sequences (214,233).…”
Section: Effect Of Time-sharingmentioning
confidence: 98%
“…With only few exceptions (16,252), the authors of the above-mentioned studes reported results basically in accordance with Baddeley's original finding: with addtional task load, randomization performance deched. In some experiments, specifically the instruction to remember a distracting text (as opposed to simply read it) would lead to enhanced redundancy of sequences (214,233).…”
Section: Effect Of Time-sharingmentioning
confidence: 98%
“…These results have not been found in several other studies, however (Baker, 1967;Beijk-Docter & Elshout) 1969). In addition, a number of other studies have produced data on this issue (Beck, 1970;Duvall, 1969;Gardner, Holzman, Klein, Linton, & Spence, 1959;Goodenough & Karp, 1961;Harpenau, 1967;Imam, 1973;Keiser, 1969;Klein, 1963;Mendelsohn, Griswold, & Anderson, 1966;Mohr, 1965;Rosett, Robbins, & Watson, 1968;Schimek & Wachtel, 1969;Valinsky, 1971;Weiss, 1970;. 1965).…”
Section: Memory For Socially Relevant Stimulimentioning
confidence: 99%
“…In this procedure, the subject's choice of alternative reactions to each of a series of social-interaction situations which best represents how he himself would react in that situation is rated as showing the use of the defenses (among others) of "reversal" (repression and denial), "principalization lt (isolation and intel-list of double-entendre words, one of whose meanings was sexual, field-dependent subjects did not respond with sexual words until later in the list, compared to field-independent subjects. Also subject to the same interpretation is the finding by Schimek and Wachtel (1969) that field-independent subjects did better than field-dependent ones in comprehending and recalling a sexual passage presented as a distraction to or in competition with a focal task, although no difference was found between the two kinds of subjects when the passage was a neutral one.…”
Section: Specialized Defensesmentioning
confidence: 96%
“…Evidence relevant to the issue of defenses has also come from studies of the effects of stress upon recall and perception. These studies have shown that field-dependent people, compared to field-independent ones, are more likely to forget previously learned stressful than neutral material (e.g., Duvall, 1969;Rosen, 1963;Schimek & Wachtel, 1969;Uhlmann & Saltz, 1965). Fielddependent people have also been shown to be more affected by stressful material in perception (e.g., Almgren, 1971;Duvall, 1969;Lefcourt, Gronnerud, & Mc-Donald, 1973;Minard &Mooney, 1969).…”
Section: Structured Controls and Specialized Defensesmentioning
confidence: 99%